Morphometric and gravimetric indices of two populations of rice frog (Fejervarya limnocharis) naturally exposed to different environmental cadmium levels - Mohd Sham Othman,; Wichase Khonsue,; Jirarach Kitana,; Kumthorn Thirakhupt,; Robson, Mark Gregory; Noppadon Kitana, (Penerbit Universiti Kebangsaan Malaysia, 2016)
In this study, morphometric and gravimetric indices were used to determine the impact of cadmium exposure on a sentinel species. Scaling coefficient, condition factor (CF), hepatosomatic index (HSI), renosomatic index (RSI) and gonadosomatic index (GSI) were compared between rice frogs (Fejervarya limnocharis) exposed to different environmental cadmium levels. The result showed that frogs caught from the contaminated site had significantly higher CF (10.296), RSI (0.413) and female GSI (7.594) than frogs from the contaminated site (7.594, 0.380 and 1.594, respectively). For Scaling Coefficient and HSI, albeit being statistically insignificant, these indices showed a similar trend. On the other hand, the male GSI showed a reverse trend where frogs from contaminated site showed higher values than their counterpart from the reference site. However, the differences were not statistically significant. This research concluded that there is a relationship between cadmium contamination with morphometric and gravimetric indices. Therefore, it is suggested that the use of these data could give an idea on the effect of cadmium exposure on the rice frog.